2009
DOI: 10.1016/j.schres.2008.10.017
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal pitch mismatch negativity in individuals with schizotypal personality disorder

Abstract: Background The goal of the study was to examine mismatch negativity (MMN) in schizotypal personality disorder (SPD) individuals. Abnormal MMN has been a consistent finding in chronic schizophrenia and there are also have been reports of reduced duration MMN in first episode schizophrenia patients (Umbricht & Krljes, 2005), with some studies finding no pitch MMN amplitude differences (Salisbury et al., 2002) while others reporting a modest reduction (Umbricht et al., 2006) in recent onset schizophrenia patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 41 publications
2
15
0
Order By: Relevance
“…Our study that included a much larger group of family members revealed essentially the same pattern. One study in SSP subjects also showed reduced MMN (Niznikiewicz et al 2009), which was also replicated by the current sample. Therefore, our study provided simultaneous replication of several key features of MMN previously found in schizophrenia patients, their family members, and in individuals with SSP traits.…”
Section: Discussionsupporting
confidence: 83%
“…Our study that included a much larger group of family members revealed essentially the same pattern. One study in SSP subjects also showed reduced MMN (Niznikiewicz et al 2009), which was also replicated by the current sample. Therefore, our study provided simultaneous replication of several key features of MMN previously found in schizophrenia patients, their family members, and in individuals with SSP traits.…”
Section: Discussionsupporting
confidence: 83%
“…34 Of the remaining 20 articles, one measured MMN in prodromal patients, 36 another in individuals who were ultra-high-risk of developing schizophrenia, 36 and another was on schizotypal personality disorders. 37 One article did contain first-episode patients, but combined MMN responses with those from individuals with chronic schizophrenia. 38 Sixteen studies remained that were further assessed.…”
Section: Methodsmentioning
confidence: 99%
“…Brenner et al (2003) reported that ASSR power to amplitude modulated tones was unaffected across a wide range of stimulus frequencies in a small sample of persons with SPD ( n =11). However, abnormalities in auditory EEG and event-related potential (ERP) response (Niznikiewicz et al, 2009; Shin et al, 2010) and reduced volume of the superior temporal gyrus (Dickey et al, 2002; Goldstein et al, 2009; Takahashi et al, 2010) in SPD suggest potential impairment in the auditory pathways. First-degree relatives of schizophrenia patients share genetic and environmental risk factors with SZ patients in the absence of psychosis and are not typically prescribed antipsychotic medications.…”
Section: Introductionmentioning
confidence: 99%